Determinan Keputusan Pembelian Sepatu Lokal Aerostreet: Peran Social Media Marketing Tiktok, Citra Merek, dan Kelompok Referensi - M. Muzakir; Nurrahmi Hayani (Al-Manar Journal of Public Administration and Management, 2025)
This study aims to examine the effect of TikTok Social Media Marketing, Brand Image, and Reference Groups on the Purchase Decision of Aerostreet local shoes among students in Pekanbaru City. The research employs a quantitative approach using a survey method. The sample consists of 100 respondents selected through purposive sampling, specifically students who had purchased Aerostreet shoes during the 2024–2025 period. Data were collected using an online questionnaire with a Likert scale and analysed using multiple linear regression with SPSS version 20. The results indicate that, partially, Social Media Marketing, Brand Image, and Reference Groups have a positive and significant effect on Purchase Decisions. Simultaneously, the three independent variables also show a significant effect, as indicated by an F-value of 99.254 with a significance level of 0.000. The Adjusted R Square value of 0.749 indicates that 74.9% of the variation in purchasing decisions can be explained by these variables, while the remaining percentage is influenced by other factors outside the model. These findings confirm that digital marketing strategies, a strong brand image, and social influence play a crucial role in shaping consumers’ purchasing decisions for local footwear products.